(untitled) (Bangladesh Journal of Anatomy, 2021)
Background: Overweight and obesity are related with the degeneration of lumbar disc, lumbar lordosis, low back pain and other higher risk problems of spine. Radiology is the gold standard method by which the lumbar lordosis angle (LLA) can be measured for diagnosis and treatment. Objective: The present study was carried out to find out the effect of overweight and obesity on lumbar lordosis angle radiologically in both sexes of adult Bangladeshi people. Materials and Methods: This cross sectional analytical study was conducted at Department of Anatomy of Rangpur Medical College, Rangpur from a period of July 2018 to June 2019. One twenty four (124) digital radiographs of both sexes, age ranging from 20 to 45 years were taken. LLA was measured in lateral view of lumbar spine. Body mass index was calculated and subjects were grouped according to BMI into group A-normal weight, group B-overweight, group C-obese. The data were analyzed and comparison between three group of both sexes was done. Result: The mean value of LLA was gradually decreased in overweight and obese than normal weight in both sex. In female statistically significant lower value was found in obese group than normal weight group. Conclusion: Study findings reveal that high BMI causing losses of natural resilience and flexibility of lumbar spine. Bangladesh Journal of Anatomy July 2021, Vol. 19, No. 2, pp. 49-52